(x²+x+1)² ÷ x²-x+1 me ajuda pfvr
Soluções para a tarefa
Respondido por
1
Olá!
(x² + x + 1)² ÷ x² - x + 1 =
( +
+
+ 2x² · x + 2x² · 1 + 2x · 1) ÷ x² - x + 1 =
( +
+ 1 + 2x³ + 2x + 2x) ÷ x² - x + 1 =
( + 2x³ + 4x + 1) ÷ x² - x + 1 =
x² + 2x + +
- x + 1 =
x² + 2x + +
- x + 1 =
x² + x + +
+ 1 =
+
+
+
=
x²x² + x²x + 4x + x² =
+
+ x² + 4x
Abraços!
gabrielgomes3316:
obrigado
Perguntas interessantes
História,
9 meses atrás
História,
9 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Português,
1 ano atrás